Predicting Students’ Pro-Environmental Attitudes Based on Environmental Personality and Personal Responsibility Mediated by Locus of Control - Damianus Dai Koban; Erian Fatria; Agus Priadi; Guspri Devi Artanti; Eka Apriyanti (Flourishing Journal, 2026)
Climate change and the increasing frequency of hydrometeorological disasters are widely recognized as threats to ecosystems and human life. One of the underlying causes is the lack of pro-environmental attitudes within society. This study examined the determinants of students’ pro-environmental attitudes by investigating the roles of environmental personality and personal responsibility, with locus of control as a mediating variable. A quantitative causal research design was employed to test a hypothetical model based on environmental education theories. The sample consisted of 65 students from SMK Negeri Semendawai, East OKU, South Sumatra, Indonesia, selected through multistage random sampling. The findings revealed that personal responsibility (PR) was the strongest and only significant predictor of students’ pro-environmental attitudes (PEA), exceeding the influence of environmental personality (EP) and locus of control (LOC), both of which had direct but non-significant effects. Furthermore, LOC did not mediate the relationship between the independent variables and pro-environmental attitudes, possibly due to situational constraints and limited supporting facilities. These findings suggest that environmental education should move beyond cognitive instruction toward affective learning that strengthens students’ sense of ownership and personal responsibility through practical environmental experiences. Abstrak Perubahan iklim dan berbagai bencana hidrometerologi yang terjadi saat ini diyakini sebagai sebuah fenomena yang dapat merusak seluruh tatanan ekologi dan kehidupan di permukaan bumi. Salah satu faktor yang diduga menjadi akar masalah ini adalah sikap masyarakat yang kurang pro-lingkungan. Tujuan penelitian ini adalah untuk menyelidiki faktor-faktor determinan sikap pro lingkungan didasarkan kepribadian lingkungan dan tanggung jawab pribadi dengan mediasi locus of control. Metode penelitian yang digunakan adalah metode kuantitatif dengan pendekatan studi kausal yang mengkonfirmasi beberapa model pendidikan lingkungan sebagai rujukan dalam membangun model hipotetik penelitian. Sampel penelitian ini melibatkan 65 siswa SMK Negeri Semendawai, OKU Timur, Provinsi Sumatera Selatan yang dipilih secara multistage random sampling. Hasil penelitian menunjukkan bahwa tanggung jawab pribadi (PR) merupakan prediktor tunggal yang paling kuat dan signifikan dalam membentuk sikap pro-lingkungan (PEA) siswa, mengungguli faktor kepribadian lingkungan (EP) dan locus of control (LOC) yang berpengaruh langsung namun tidak signifikan. Selain itu, LOC gagal berfungsi sebagai variabel mediator dalam model ini, yang diduga akibat adanya hambatan situasional dan kurangnya fasilitas pendukung. Implikasinya, pendidikan lingkungan di sekolah perlu bertransformasi dari edukasi kognitif ke pendekatan afektif yang memperkuat rasa memiliki dan tanggung jawab personal melalui pengalaman praktis.